Adsorption of metal atoms on MoSi2N4 monolayer: A first principles study. (December 2022) - Cui, Zhen; Yang, Kunqi; Ren, Kai; Zhang, Shuang; Wang, Lu
Abstract: The magnetic and electronic behaviors of metal atoms adsorbed MoSi2 N4 monolayer have been systematically researched by density functional theory. The results reveal that the most stable sites of MoSi2 N4 monolayer adsorbed by various metal are diverse. The band structures of the Li–MoSi2 N4 system exhibit the nonmagnetic metal behavior, while the Pd–MoSi2 N4, Pt–MoSi2 N4, and Zn–MoSi2 N4 systems indicate nonmagnetic semiconductors. Meanwhile, K–MoSi2 N4 and Na–MoSi2 N4 systems emerge magnetic metal character, and the Ag–MoSi2 N4, Au–MoSi2 N4, Bi–MoSi2 N4, Fe–MoSi2 N4, Mn–MoSi2 N4, Pb–MoSi2 N4, and V–MoSi2 N4 systems appear magnetic semiconductor features, while the magnetic moments are 1.00 μB, 1.00 μB, 1.00 μB, 3.00 μB, 5.87 μB, 4.26 μB, 0.37 μB, 0.52 μB, 1.94 μB, 2.86 μB, 3.85 μB, and 4.84 μB, respectively. Furthermore, the charge transfer arises between the metal atoms and MoSi2 N4 . Importantly, the work function of MoSi2 N4 system decreases greatly after metal adsorption, in particular, the work function of Li–MoSi2 N4 is lower 74.95% than that of pristine MoSi2 N4 . Therefore, it indicates that metal atoms adsorbed MoSi2 N4 systems can be used to manufacture spintronic and vacuum electron emission nanodevices. Graphical abstract: Image 1 Highlights: The Pd–MoSi2 N4, Pt–MoSi2 N4, and Zn–MoSi2 N4 systems indicate nonmagnetic semiconductors. The Ag–MoSi2 N4, Au–MoSi2 N4, Bi–MoSi2 N4, Fe–MoSi2 N4, Mn–MoSi2 N4, Pb–MoSi2 N4, and V–MoSi2 N4 systems appear magnetic semiconductor features. The work function of MoSi2 N4 system decreases greatly after metal adsorption, in particular, the work function of Li–MoSi2 N4 is lower 74.95% than that of pristine MoSi2 N4 .